Evaluation of Zakat Management Program in The Badan Amil Zakat National of Banten Province - Muammar, Ahmad Nurul; Widodo, Joko; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2018)
In the Islamic religion of zakat one of the pillars required for every Muslim (As'ad, 1980: 01), Hasan (2010) defines that zakat has a special place on Islamic principles, and is the main tool for ensuring social justice in Islam. The purpose of this research is to make the evaluation instrument of zakat management program at Badan Amil Zakat Nasional (BAZNAS) Provinsi Banten fulfilling valid condition and effectiveness assessment test with evaluation of Context Input Process Product (CIPP) model. This research using Mixed Methods is a procedure for collecting, analyzing, and